Cryopreservation of tropical plant germplasm: Current research progress and applications - Engelmann, F.; Takagi, H.; Japan International Research Center for Agricultural Sciences; International Plant Genetic Resources Institute (2000)
This publication includes the papers presented during an international workshop held in Tsukuba, Japan in October, 1998 which was jointly organized by JIRCAS and IPGRI. This meeting aimed at assessing the state of the science, exploring cryopreservation applications, examining outstanding problems and identifying priority areas for collaborative research, technology development, transfer and application. The resulting volume is a synthesis of new and original information in the area of cryopreservation of tropical plant germplasm.